Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

L’implantation du Projet transdisciplinaire en santé communautaire à l’Université de Saint-Boniface - Archambault, Hélène; de Rocquigny, Janelle; Ba, Halimatou; Giasson, Florette; Lapointe, Gisèle (Reflets, 2014)

Un mal intolérable : revendiquer des services en santé mentale pour la jeunesse franco-ontarienne avant la crise de l’Hôpital Montfort - Arsenault, Mathieu; Martel, Marcel (Minorités linguistiques et société, 2018)
Dans les années 1970, la question de l’accès aux soins de santé mentale en français pour la minorité francophone émerge dans l’espace ontarien, notamment grâce aux pressions de l’ACFO et au rapport Dubois sur les services de santé en français. Dès lors, la question des soins de santé mentale pour la jeunesse constitue un aspect crucial de la bataille pour l’accès à des soins de santé en français. Symbole par excellence du sujet minoritaire, le jeune Franco-Ontarien s’impose comme catalyseur du discours de la classe politique, des groupes d’intérêts et des parents qui écrivent au ministre provincial de la Santé pour revendiquer des services de santé mentale en français et pour réclamer la mise en place d’une politique-cadre en matière de santé. Mots-clés : santé mentale, jeunesse, Franco-Ontarien, services en français, correspondance

New Brunswick's elders neglected and forgotten - Association francophone des aînés du Nouveau-Brunswick (Comité d'action sur la bienveillance envers les personnes aînées, 2022)

Vieillir dans l'indifférence et l'indignité au Nouveau-Brunswick - Association francophone des aînés du Nouveau-Brunswick (Comité d'action sur la bienveillance envers les personnes aînées, 2022)

Soins à domicile en français. Rapport final - Atlantic Evaluation Group Inc (2013)

Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

État de la situation et étude de modèles de soins de santé primaires offerts aux francophones vivant en situation minoritaire au Canada - Axion (2016)

Newcomers and social and health pressures in Franco-Manitoban communities: Overview of avenues of research and preliminary considerations - Bahi, Boniface (Canadian Issues, 2008)
This article outlines theoretical considerations and preliminary data for a research project undertaken at the request of the research office at the Collège universitaire de Saint-Boniface in Winnipeg, with the support of the Corporation Catholique de la Santé du Manitoba. The Corporation's "Étude d'évaluation stratégique sur l'intégration des médecines alternatives à la médecine officielle (2006-2009)" seeks to build the capacities of public medical institutions in view of, among other things, socio-demographic changes caused by the arrival of newcomers. The study, now in progress, is already concerned with the potential clientele for the alternative health services that would be integrated into what is regarded as officiai medicine. Our research project, entitled "Nouveaux arrivants et pathologies émergentes en milieu franco-manitobain: Quelles exigences?" seeks to identify newcomers' implicit (unexpressed) and explicit (known) demands regarding sociocultural and health services available in the Franco-Manitoban host community. The first step involves collecting basic data on migration trends and their multidimensional implications at the community level. This article will, therefore, focus on contrasting local social and health services with the direct and indirect demands of newcomers. It will attempt to identify requirements for community, social and institutional development. The abovementioned theoretical considerations relate to the issues, objectives and approach of our research project. The preliminary data consist of information obtained from Accueil francophone and from several immigrants, such as the excerpt at the beginning of this paper.

Facteurs favorisant l’offre de services de santé en français : études de cas en milieu hospitalier anglophone - Bahi, Boniface; Forgues, Éric (Minorités linguistiques et société, 2015)
Par une approche à la fois qualitative et quantitative, la présente étude analyse les modalités de prise en compte de la langue dans l’organisation des services de santé au sein des établissements majoritairement anglophones, de même que les possibilités favorables à l’offre de services de santé en français en milieu minoritaire francophone. L’examen des facteurs favorisant l’offre de services de santé en français en milieu minoritaire francophone porte sur les dimensions organisationnelles (internales) et sur les dimensions environnementales (externales) du milieu hospitalier. Ces possibilités et ces facteurs favorables ont trait notamment à la volonté de l’administration et des professionnels de la santé des établissements hospitaliers, au renforcement et à la mise en valeur du bilinguisme dans la gestion des services, mais aussi à l’émergence aussi bien d’une demande active de services en français que d’une volonté politique, juridique et réglementaire des autorités gouvernementales. Mots-clés : santé, services en français, milieu minoritaire, francophonie, offre active

The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Formation linguistique, adaptation culturelle et services de santé en français - Beaulieu, Marielle (Consortium national de formation en santé et Société Santé en français, 2010)

Enquête sur l’offre active pour les services auxiliaires de santé du Nord-Est de l’Ontario - Bélanger, Roxanne; Mayer-Crittenden, Chantal; Mainguy, Josée; Coutu, Anie (Reflets, 2018)
Au Canada, il existe peu de données décrivant les services auxiliaires de santé en français disponibles dans les communautés francophones en situation minoritaire. L’objectif de cette étude était d’examiner l’accès aux services d’orthophonie, de physiothérapie et d’ergothérapie en français dans le Nord-Est de l’Ontario. Un outil mesurant la disponibilité et l’offre active des services a été créé et validé. Ce dernier a été distribué aux personnes fournissant les services et aux personnes les utilisant afin de déterminer leurs perceptions concernant l’offre de ces services en français, ainsi que l’accessibilité aux services auxiliaires de santé en français. Les résultats ont montré un manque de services en français dans cette région. Mots-clés : situation minoritaire francophone, services auxiliaires de santé, offre active, Nord-Est de l’Ontario, questionnaires

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 21 : ConnectAînés / Francsavoir (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Pratique # 22 : Bien vieillir chez soi / Soutien à domicile (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Points saillants sur la santé mentale des jeunes franco-canadiens d’est en ouest du pays : le témoignage de nos assistantes de recherche - Benoit, Monique; Beaton, Ann. M. (Minorités linguistiques et société, 2018)

Les inégalités sociales de santé chez les communautés francophones en situation minoritaire (CFSM) au Canada [numéro thématique] - Benoit, Monique; Bouchard, Louise; Garceau, Marie-Luce (Reflets, 2012)

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Programme d’accès aux services de santé et aux services sociaux en langue anglaise de la Côte-Nord - Bilodeau, Nancy; Paradis, Pascal; Morin, Sandra (Agence de la santé et des services sociaux de la Côte-Nord, 2011)

L'offre active de services en français : la clé de voûte à l'atteinte des objectifs de la Loi sur les services en français de l'Ontario - Boileau, François (Commissariat aux services en français de l'Ontario, 2016)

Special report on French language health services planning in Ontario, 2009 - Boileau, François (Office of the French Language Services Commissioner, 2009)

Littératie en matière de santé : des moyens novateurs de stimuler la prise en charge par la population francophone du Nord-Est du Nouveau-Brunswick - Boivin, Nathalie; Réseau Communauté en santé de Bathurst (Francophonies d'Amérique, 2009)
L’Organisation mondiale de la santé (OMS) définit la promotion de la santé comme le processus qui confère aux populations les moyens d’assurer une plus grande maîtrise de leur propre santé et de l’améliorer. Or, comment parler de prise en charge de sa santé alors qu’une partie importante de la population francophone du nord-est du Nouveau-Brunswick ne possède pas le niveau minimal d’alphabétisation requis pour fonctionner dans notre société actuelle ? Une démarche habilitante auprès de cette population a été menée. Les résultats préliminaires sont exposés, dévoilant les avantages et les obstacles d’une campagne médiatique.

L'offre active des services de santé en français en Ontario : une mesure d'équité - Bouchard, Louise; Beaulieu, Marielle; Desmeules, Martin (Reflets, 2012)
Cet article fait état d’une recherche sur l’offre active de services en français en Ontario. L’étude avait pour objectifs de recenser les définitions de l’offre active de services en français; d’identifier les pratiques d’offre active (facilitateurs ou obstacles); d’identifier les indicateurs de mesure de l’offre active et de proposer des recommandations permettant d’améliorer l’offre active de services en français. À cette fin, une revue documentaire, une enquête auprès de professionnels oeuvrant dans le domaine de la planification des services de santé en français ainsi qu’un atelier de cartographie conceptuelle ont été entrepris. Mots-clés : minorité linguistique, services de santé, offre active, Loi 8

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

État des connaissances sur la santé et les services de santé aux aînés francophones en contexte linguistique minoritaire - Bouchard, Louise; Savard, Jacinthe; Renaud, Alexandre (Reflets, 2022)
La recherche en santé sur les communautés de langue officielle en situation minoritaire (CLOSM) a connu un essor remarquable ces deux dernières décennies. L’objectif de cet article est de présenter un état des lieux de la recherche effectuée sur la problématique de la santé et des soins destinés aux personnes âgées francophones en situation linguistique minoritaire. Différents thèmes sont abordés tels que la santé et ses déterminants, l’expérience des usagers quant à la langue des services, l’environnement légal et politique des services en français, l’organisation des services et la performance du système de santé. Cette synthèse évaluative de la recherche vise à fournir un outil de mobilisation des connaissances et des pistes d’action pour mieux répondre aux besoins des populations aînées et pour améliorer l’offre de services. Mots-clés : revue de littérature, aînés francophones, santé, services et politiques de santé, minorité de langue officielle, Canada

Conclusion : des connaissances nouvelles pour des services en français de qualité et sécuritaires à l’intention des communautés francophones en situation minoritaire - Bouchard, Pier; Savard, Jacinthe; Savard, Sébastien; Vézina, Sylvain; Drolet, Marie (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Le cadre théorique en filigrane de cet ouvrage, soit le modèle de l’analyse stratégique, est repris la conclusion et contribuer à améliorer la compréhension du rôle de l’acteur et du système dans l’actualisation des principes de l’offre active de services sociaux et de santé dans la langue au choix de l’usager. Le chapitre aborde les enjeux de l'accès à des services sociaux et de santé en français, le jeu des acteurs au sein des communautés francophones en situation minoritaire, le système et les leviers d'action ainsi que les stratégies en faveur de l'offre active. Plus spécificement, on articule les principales propositions contenues dans l’ouvrage autour des six stratégies suivantes : levier juridique et politique, formation et engagement des futurs professionnels, culture organisationnelle axée sur l’offre active, leadership des acteurs sociaux et de la communauté, mesures d’attraction et de rétention des intervenants et enfin mobilisation et collaboration des acteurs. En terminant, les stratégies sont énoncées en 6 recommandatons en faveur de l'offre active de services sociaux et de santé en français en contexte minoritaire.

Conclusion: New insights into safe, quality services in official language minority communities - Bouchard, Pier; Savard, Jacinthe; Savard, Sébastien; Vézina, Sylvain; Drolet, Marie (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

Repérage et analyse de l'information sur la santé dans Internet : le cas des CLOSM dans la province de l'Alberta - Bowker, Lynne (Francophonies d'Amérique, 2009)
La présente étude examine, dans le contexte des langues officielles, quelques-uns des besoins insatisfaits des communautés de langue officielle en situation minoritaire (CLOSM) au Canada sur le plan de la santé. Nous présentons les résultats d’une analyse de l’information sur la santé offerte dans Internet aux francophones de l’Alberta. Nous avons procédé à une évaluation comparative de l’information sur la santé destinée à la population albertaine en français et en anglais dans Internet. En présentant les résultats, cette analyse compare le nombre de textes en français et en anglais et se penche sur la qualité de la langue des textes en français.

An analysis of crisis services accessibility of new francophone arrivals in the city of Winnipeg - Buissé, Diane M.N. (University of Manitoba, 2005)

L'offre active de services de santé mentale en français en Ontario et au Manitoba : les rôles clés des instruments et des outils - Cardinal, Linda; de Moissac, Danielle; Deschênes-Thériault, Guillaume (Administration publique du Canada / Canadian Public Administration, 2023)
Cet article présente les données d'un sondage réalisé en 2019 sur la connaissance des gestionnaires et des professionnels œuvrant dans le domaine de la santé mentale en Ontario et au Manitoba de leurs obligations linguistiques et des outils qui favorisent la pratique de l'offre active de services français. L'étude permet de souligner que plus les professionnels et les gestionnaires comprennent leurs obligations, tant en Ontario qu'au Manitoba, plus ils peuvent profiter des outils existants pour s'en acquitter. L'étude montre qu'il existe en effet un lien entre la connaissance des obligations et l'utilisation des outils pour faire de l'offre active de services de santé mentale en français. Elle permet aussi d'insister sur le rôle clé des outils pour faire de l'offre active de services en français.

Le rôle des intervenantes du secteur de la violence faite aux femmes dans le développement des services en français en Ontario : une étude exploratoire - Cardinal, Linda; Garceau, Marie-Luce; Sirois, Ghislaine; Plante, Nathalie (Reflets, 2015)
L’article porte sur le rôle des intervenantes francophones du secteur de la violence faite aux femmes (VFF) dans le développement de services en français en Ontario. Depuis les années 1990, ce secteur a fait des avancées importantes dans le développement de services en français, et peut désormais venir en aide à de plus en plus de femmes francophones. Or, il existe peu d’études portant sur le rôle des intervenantes dans le développement de ces services en français. Cette première analyse de la situation repose sur les résultats d’entretiens menés auprès de 14 intervenantes francophones du secteur de la VFF. Ces entretiens permettent de commencer à prendre la mesure de leur rôle dans le développement des services en français dans le secteur de la VFF. Les données portent sur les modes d’action des intervenantes ainsi que les savoirs ou apprentissages qu’elles tirent de leurs efforts afin de les transmettre à d’autres et ainsi encourager la réflexion sur les enjeux liés au développement des services en français en Ontario. Mots-clés : développement de services en français, intervenantes, modes d’action, savoirs et apprentissages, violence faite aux femmes, Ontario français, Ontario

L’offre active de services de santé mentale en français en Ontario : données et enjeux - Cardinal, Linda; Normand, Martin; Gauthier, Alain P.; Laforest, Rachel; Huot, Suzanne; Prud’homme, Denis; Castonguay, Marcel; Eddie, Marie-Hélène; Savard, Jacinthe; Yaya, Sanni (Minorités linguistiques et société, 2018)
Au Canada, au gouvernement fédéral et dans plusieurs provinces, le principe d’offre active sert à guider la prestation des services publics en français. L’Ontario se démarque, car son approche est en partie volontaire. Il importe donc d’étudier comment les services en français sont intégrés à la gouvernance des services publics au sein de la province. Cet article puise dans les données gouvernementales existantes afin de brosser un tableau de l’offre active de services en français en santé mentale. Or, les auteurs montrent que ces données sont difficiles à obtenir et parcellaires. L’article sert à souligner des défis importants pour l’offre de services en français dans le domaine de la santé mentale en Ontario. Mots-clés : offre active, services en français, santé mentale, Ontario, données

Modèle d’apport de services en santé communautaires aux francophones du Sud de l’Ontario : entrevue avec Janet Rajroop - Casimiro, Lynn (Reflets, 2002)

Le recensement des outils de travail disponibles en français pour les professionnels oeuvrant dans le domaine de la santé : un rapport de la méthodologie utilisée par les physiothérapeutes - Casimiro, Lynn; Fortin, Murielle; Moisan, France; Tremblay, Louis E. (Reflets, 2002)

Profil génétique et prévalence de la fibrose kystique dans les communautés acadiennes et francophones des Maritimes - Chappe, Frédéric; McGrath, Karla; Robinson, Walter; Chappe, Valérie (Francophone d'Amérique, 2009)
Nous évaluons ici la situation des Acadiens et des francophones des provinces maritimes (Nouvelle-Écosse, Nouveau-Brunswick, Île-du-Prince-Édouard) face à la fibrose kystique, la maladie génétique létale la plus répandue en Amérique du Nord. Nos résultats indiquent que plusieurs familles acadiennes et francophones sont touchées par cette maladie et qu’il existe un besoin de documentation et de services en français, spécifiques aux communautés acadiennes. Des disparités régionales ont été observées pour l’âge au diagnostic et le profil génétique, notamment dans les régions à majorité francophone. Cette analyse confirme le besoin d’études spécifiques sur la santé des Acadiens et des francophones des Maritimes.

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

Perceptions des professionnels de la santé quant aux besoins oncologiques pédiatriques offerts en français à domicile : étude descriptive qualitative - Chartrand, Julie; Jibb, Lindsay; Grandmont, Camille; Hardy-Bélanger, Élisabeth; Cheng, Sara; Balasa, Rebecca; Johnston, Donna (Revue canadienne de soins infirmers en oncologie, 2022)

Enquête exploratoire sur le recueil de la variable linguistique dans les données administratives des hôpitaux de la région du RLISS-Champlain - Chomienne, Marie-Hélène; LeClerc, Chantale; Schnarch, Brian; Bouchard, Louise; McKay, Martine; Farmanova, Elina (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, Réseau local d’intégration des services de santé de Champlain, 2011)

Les priorités de recherche sur la santé des francophones en Ontario - Chomienne, Marie-Hélène; Luyinga, A.; Farmanova, Elina (Bureau des services en français du Ministère de la santé et des soins de longue durée de l’Ontario et Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2011)

Améliorer les services et les soins offerts aux communautés francophones en situation minoritaire au Canada : entre recherche, dialogue et formation. - Collin, Stéphanie; Bouchard, Pier; Vézina, Sylvain; Cormier, Manon (Minorités linguistiques et société, 2024)
Au regard de l’amélioration des services et soins de santé offerts aux communautés francophones en situation minoritaire (CFSM), la programmation du Groupe de recherche et d’innovation sur l’organisation des services de santé (GRIOSS) de l’Université de Moncton a constamment évolué. Depuis 2009, les travaux de l’équipe de recherche ont été névralgiques, développant une compréhension plus fine de divers enjeux « évolutifs du terrain » s’inscrivant dans des thèmes généraux comme la gestion et l’organisation des services et soins de santé ainsi que la gouvernance. Cet article présente, sous forme d’un récit historique, l’évolution de la programmation de recherche du GRIOSS et une synthèse des résultats de recherche ainsi que des extrants ayant influencé la pratique. Un élément central du bilan : les savoirs issus de ces recherches ont servi, au fil du temps, à nourrir la réflexion commune et le dialogue s’est traduit par des changements sociaux durables au sein des CFSM. Mots-clés : communautés francophones en situation minoritaire, accès aux services de santé dans la langue officielle de son choix, offre active, recherche-action, dialogue

Accès aux services de santé en français et gouverne en réseau : différentes représentations et stratégies d'action - Collin, Stéphanie; Grenier, Gabrielle; McIntyre, Martine; Roy, Shanie (Revue Gouvernance, 2022)
Au Canada, l’enjeu de l’amélioration de l’accès aux services de santé en français, surtout dans les provinces hors Québec, s’inscrit dans des relations complexes entre différents acteurs qui poursuivent des objectifs variés. En 2008, au Nouveau-Brunswick, l’État a remplacé les huit régies régionales existantes par deux nouvelles régies, soit la Régie régionale de la santé A (Réseau de santé Vitalité) et la Régie régionale de la santé B (Réseau de santé Horizon). Plus tard, il a été établi que Vitalité fonctionnerait en français et Horizon en anglais, et que les réseaux assureraient la prestation des services de santé dans la langue officielle du choix des citoyens. Ainsi, l’objectif général de la recherche était de comprendre l’influence des dynamiques entre les acteurs d’une gouverne en réseau sur le traitement de l’enjeu que représente l’accès aux services de santé en français. Une méthode qualitative comprenant notamment des entretiens semi-directifs (n=26) a été retenue. Les résultats montrent que, d’une part, l’offre de services dans la langue du choix des citoyens, qui est conditionnée par le cadre juridique sur les droits linguistiques, pousse les acteurs à mobiliser des stratégies axées sur la qualité et la sécurité. D’autre part, l’accès révèle une dimension symbolique, puisqu’il est associé aux notions d’équité et de gouvernance. L’accès aux services de santé en français est un sujet délicat pour l’État, qui demeure en retrait par rapport à celui-ci. Afin de mieux répondre aux besoins en santé des citoyens, cet acteur doit faire émerger des liens de confiance et formuler des objectifs clairs. Mots-clés : gouverne, réseau, accès, santé, communautés francophones en situation minoritaire, langues officielles

L’offre active une culture de respect, une culture d’excellence : dépliant [infographie] - Commissariat aux langues officielles (2019)

L’offre active une culture de respect, une culture d’excellence : guide complet [infographie] - Commissariat aux langues officielles (2017)

Promoting the health and well-being of English-speaking Seniors in Quebec. A community model (infographic) - Community Health And Social Services Network/Réseau communautaire de santé et de services sociaux (2019)

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

La formation à l’offre active de services de santé et de services sociaux en français — La valeur ajoutée du Consortium national de formation en santé (CNFS) - Consortium national de formation en santé (Reflets, 2014)

Coup d’œil sur la recherche : Qualité et sécurité des soins de longue durée en Ontario [infographie] - Consortium national de formation en santé; van Kemenade, Solange (2022)

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Portrait des minorités de langue officielle au Canada : les francophones de l'Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Francophones in Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Analytical Paper, 2010)

Access to resources in the community through navigation: Protocol for a mixed-methods feasibility study - Dahrouge, Simone; Gauthier, Alain; Chiocchio, François; Presseau, Justin; Kendall, Claire; Lemonde, M.; Chomienne, Marie-Hélène; Perna, A.; Toal-Sullivan, Darene; Devlin, R. A.; Timony, Patrick; Prud'homme, Denis (JMIR Publications, 2019)
Background: Community-based health and social resources can help individuals with complex health and social needs achieve their health goals. However, there is often inadequate access to these resources due to a lack of physician and patient awareness of available resources and the presence of social barriers that limit an individual’s ability to reach these services. Navigation services, where a person is tasked with helping connect patients to community resources, embedded within primary care may facilitate access and strengthen the continuity of care for patients. Objective: This study aims to describe the protocol to assess whether the implementation of the Access to Resources in the Community (ARC) navigation model (an innovative approach to navigation services) is feasible, including its potential to achieve its intended outcomes, and to assess the viability of the evaluation approach. Methods: The study consists of a single-arm, prospective, explanatory, mixed-methods, pre-post design feasibility study focusing on primary care practice settings with vulnerable populations. Participants include primary care providers and patients. Results: Enrollment is closed with 82 patients. Navigation services have ended for 69 patients. Conclusions: The study of an innovative complex intervention requires an adequate assessment of the feasibility of the intended approach during which the potential challenges of the planned intervention and need for its adaptation may be uncovered. Undertaking a feasibility study of the ARC navigation model from a conceptually clear and methodologically solid protocol will inform on the practicality and acceptability of the approach, demand for the services, ease of implementation, quality of integration of the new services within primary care, and practicality and potential for efficacy prior to initiating a randomized controlled trial.

Accès aux services de santé et d’interprète accompagnateur : l’expérience des communautés minoritaires à faible densité de francophones au Canada. Rapport de recherche-Projet INTACC - de Moissac, Danielle (Société Santé en français, 2016)

Access to health and interpreter-companion services – the experience of sparsely populated Francophone minority communities in Canada - de Moissac, Danielle (Société Santé en français, 2016)

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Disponibilité et accessibilité des services de santé en français au Manitoba. Rapport final - de Moissac, Danielle; de Rocquigny, Janelle; Roch-Gagné, Margaux; Giasson, Florette (Université de Saint-Boniface et Institut franco-ontarien de l’Université Laurentienne, 2011)

Enjeux et défis dans l’offre de services dans la langue de la minorité : l’expérience des professionnels bilingues dans le réseau de la santé et des services sociaux - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Le présent chapitre dévoile l’expérience de professionnels bilingues quant à l’offre de services sociaux et de santé dans la langue officielle de la minorité en contexte canadien. Soixante-douze professionnels du Manitoba et de l’Est ontarien décrivent les principaux enjeux associés à la langue et les défis auxquels ils sont confrontés quotidiennement dans l’offre active de ces services. Ces défis concernent la pénurie de professionnels et de services bilingues, la difficulté à repérer le client désirant un service dans la langue officielle de la minorité et les professionnels bilingues, ainsi que l’absence d’appui organisationnel pour faire une offre active de services dans les établissements de santé. Pour mieux soutenir l’offre de services dans la langue de la minorité, des pistes de solution sont proposées. Mots-clés : offre active, santé et services sociaux, langue officielle, contexte minoritaire, professionnels.

Issues and challenges in providing services in the minority language: The experience of bilingual professionals in the health and social service network - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

Démonstration de la valeur ajoutée de la collecte de l'identité linguistique [webinaire] - Desaulniers, Jacinthe; Manseau, Jasmin (2017)

Utilisation des services gouvernementaux de langue française. Une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités linguistiques, 2009)

Utilisation des services gouvernementaux de langue française : une étude auprès des Acadiens et francophones de la Nouvelle-Écosse sur les facteurs associés à l’utilisation des services gouvernementaux en français : sommaire - Deveau, Kenneth; Landry, Rodrigue; Allard, Réal (Institut canadien de recherche sur les minorités liguistiques, 2010)

Agir pour avoir accès à des services sociaux et de santé en français. Des francophones en situation minoritaire nous enseignent quoi faire! - Drolet, Marie; Arcand, Isabelle; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée (Revue canadienne de service social, 2015)
Même si les droits des francophones de l’Ontario sont garantis par la Loi de 1986 sur les services en français, l’accès à des services sociaux et de santé en français dans cette province s’avère complexe en raison d’importantes barrières à recevoir de tels services sur un continuum. Nous avons exploré à l’aide d’entrevues qualitatives les points de vue de 40 parents et proches aidants francophones qui vivent en contexte bilingue dans la région d’Ottawa et dont l’enfant ou l’aîné pour lequel ils ont une responsabilité d’aidant utilise des services sociaux et de santé en français. Ces francophones s’avèrent des acteurs au sein de leur trajectoire de services, adoptant cinq stratégies pour accéder à de tels services. De plus, le sentiment de confort et la relation de confiance que procure l’usage du français tout au long de l’intervention, ainsi que le soutien des professionnels francophones ont facilité leur démarche. Il n’en demeure pas moins que l’offre de services en français ne doit pas devenir la responsabilité d’individus ou d’une minorité. Mots-clés : Francophonie en situation minoritaire, accès à des services sociaux, minorité linguistique, barrières aux services, offre active de services en français, entrevues qualitatives

Problématique générale : Enjeux de l’accessibilité et de l’offre active de sociaux et de santé au sein de la francophonie canadienne en situation minoritaire - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; Laforge, M.-J. (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Cette problématique générale vise tout d’abord à présenter un portrait global des communautés francophones en situation minoritaire (CFSM) au Canada. Nous présenterons aussi la problématique de l’accessibilité à des services sociaux et de santé en français en contexte linguistique minoritaire, l’importance de l’accès à des services dans la langue officielle de son choix et les principaux éléments qui justifient le fait d’offrir activement des services sociaux et de santé en français dans les CFSM. Nous établirons également les bases d’une définition de l’offre active et certains contours politiques et historiques qui façonnent les services sociaux et de santé en français en contexte francophone minoritaire. Cette problématique générale sera, par conséquent, une assise pour chacun des chapitres qui composeront cet ouvrage et en facilitera la compréhension.

Introduction: Social services and health services in minority-language communities: Towards an understanding of the actors, the system, and the levers of action - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; van Kemenade, Solange (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Health services for linguistic minorities in a bilingual setting: Challenges for bilingual professionals - Drolet, Marie; Savard, Jacinthe; Benoît, Josée; Arcand, Isabelle; Savard, Sébastien; Lagacé, Josée; Lauzon, S.; Dubouloz, Claire-Jehanne (Qualitative Health Research, 2014)
We explore in this qualitative research the challenges faced by bilingual health and social services professionals in a Canadian bilingual setting, as well as the strategies used to overcome them. Eight focus groups were conducted with a total of 43 bilingual Francophone professionals who offered services in French in 21 health and social service organizations in eastern Ontario, Canada. We highlight linguistic issues affecting a minority Francophone clientele, the shortage of services in French, and organizational issues within these agencies. The solutions that the professionals adopt for better serving the clients and overcoming these challenges focus on adapting services from linguistic angles. In the long term, such an enhanced approach can affect staff well-being. Ensuring access to services for linguistic minority populations and the active offer of same should not rest solely on the shoulders of such professionals, but rather on organizational strategies.

L’expérience des francophones dans l’Est ontarien : importance des personnes pivots (usagers et intervenants) et influence des structures encadrant le système de santé et des services sociaux - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Le présent chapitre décrit l’expérience d’accès à des services sociaux et de santé en français de francophones de l’Est ontarien. Les expériences et les perspectives de 40 parents, aînés et proches aidants ont été recueillies à l’aide d’entrevues semi-structurées. Une analyse qualitative des verbatim ainsi qu’une analyse visuelle des trajectoires d’un sous-groupe de neuf participants ont permis de faire ressortir les facilitateurs et les défis d’accès aux services en français rencontrés par ces usagers, à partir de leur perspective ou de celle de leur proche aidant. Plus spécifiquement, ce chapitre met l’accent sur les éléments facilitateurs dans le but d’en tirer des leçons pour améliorer les services sociaux et de santé en langue officielle en situation minoritaire. Mots-clés : accès aux services en français, francophones Ontario, recherche qualitative.

The experience of Francophones in Eastern Ontario: The importance of key facilitators (service users and providers) and the influence of structures supporting the health and social services system - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Initiatives intergénérationnelles en santé. Rapport final - Duguay, Benoît (La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français, 2007)

Le projet « Préparer le terrain » : outil de planification des services de santé primaire et de mieux-être en français au Nouveau-Brunswick - Duguay, Lise (Gouvernance, santé et minorités francophones : stratégies et nouvelles pratiques de gestion au Canada, 2007)

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Soins et services pour le maintien à domicile des personnes aînées des communautés francophones en situation minoritaire. - Dupuis-Blanchard, Suzanne (Minorités linguistiques et société, 2024)
L’accès aux soins et aux services à domicile en français pour les personnes aînées des communautés francophones en situation minoritaire (CFSM) représente un défi pour le maintien à domicile. Le but de cet article est de présenter le contexte dans lequel baignent les soins et les services à domicile, de résumer l’état des connaissances sur le sujet basé sur les travaux de l’autrice, et d’offrir un aperçu de l’avenir des soins et services à domicile. Les résultats de cette synthèse de la littérature démontrent qu’il y a très peu d’écrits portant sur le maintien à domicile en CFSM alors que les personnes aînées francophones sont plus âgées que leurs homologues anglophones. Par conséquent, les travaux de l’autrice permettent d’établir une base sur laquelle de futures initiatives peuvent s’ancrer. Quant à l’avenir des soins et services à domicile, certaines perspectives permettent d’émettre quelques idées pour l’avancement des connaissances dans le domaine. Mots-clés : vieillissement, domicile, CFSM, autonomie, services

Naviguer le maintien à domicile en communautés de langue officielle en situation minoritaire rurales : enjeux et pistes de solutions - Dupuis-Blanchard, Suzanne; Caissie, Julie (Reflets, 2021)
Le vieillissement de la population dans les provinces de l’Atlantique est une réalité courante en plus d’une composition géographique rurale et la présence de communautés de langue officielle en situation minoritaire (CLOSM). Les objectifs de cette étude descriptive qualitative étaient de 1) comprendre les services utilisés pour le maintien à domicile, et 2) déterminer les services nécessitant une amélioration pour l’accès en français. Vingt-six (n=26) personnes âgées ont participé à cette étude en région rurale de l’île du Prince Édouard. Les résultats témoignent des difficultés d’accès aux services pour le maintien à domicile tout en offrant des pistes de solutions pour l’améliorer. Mots-clés : Maintien à domicile, vieillissement, communautés de langue officielle en situation minoritaire, communauté rurale, services, recherche qualitative

La recherche au profit d’un meilleur accès aux services de santé en français [numéro thématique] - Dupuis-Blanchard, Suzanne; Vézina, Sylvain (Minorités linguistiques et société / LinguisticnMinorities and Society, 2015)

Vieillir en santé en situation minoritaire linguistique au Canada : enjeux, defis et mobilisation collective - Dupuis-Blanchard, Suzanne; Villalon, Lita; Alimezelli, Hubert.Tote. (Global Health Promotion, 2014)
Au Canada, la santé des francophones et des anglophones vivant en milieu linguistique minoritaire est un sujet d’intérêt pour plusieurs chercheurs et organismes communautaires. Cet article s’inspire d’un symposium sur le thème concernant le vieillissement en santé en situation minoritaire linguistique présentée lors du 4e Colloque international des programmes locaux et régionaux de santé. Trois volets sont présentés, soit l’identification des facteurs associés à la santé perçue, le maintien à domicile et le dépistage de la malnutrition. Les résultats décrivent 1) les déterminants de la santé perçue tels que les services de santé, la vitalité de la communauté minoritaire et l’éducation ; 2) le peu de changements aux services de maintien à domicile en dépit du vieillissement de la population ; et 3) la haute prévalence de la malnutrition chez les aînés au Nouveau-Brunswick. Enfin, nous suggérons l’élaboration et l’implantation d’une politique publique du vieillissement au Canada afin d’assurer des services de qualité tout au long du continuum santé.

Leçons apprises sur la navigation des services de santé en français - Entité de planification des services de santé en français pour les régions de Waterloo, Wellington, Hamilton, Niagara, Haldimand, Brant (2019)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

Pour un meilleur accès à des services de santé en français. Étude coordonnée par la Fédération des communautés francophones et acadienne (FCFA) du Canada pour le compte du Comité consultatif des communautés francophones en situation minoritaire (CCCFSM) - Fédération des communautés francophones et acadienne du Canada (2001)

Forum on Partnering for Innovative and Collaborative Long-Term Care Solutions for Francophones - Fondation Hélène Tremblay Lavoie Foundation; Reflet Salvéo (Fondation Hélène Tremblay Lavoie Foundation, 2019)
Access to French Language Services, more specifically to long term care beds and specialized dementia care units are not equitable and accessible across the Greater Toronto Area (GTA) and do not meet the specific needs of the Francophones in terms of location and language needs. Based on the goals of laying the foundation for action-oriented public / private / not-for-profit partnerships (social enterprise), better defining the needs of the Francophone community for specialized long-term care, and exploring innovative models that can be adapted to the different needs of the community, Fondation Hélène Tremblay Lavoie Foundation organized a one-day Forum to engage with different stakeholders on November 23, 2018 in Toronto. The one-day Forum ensured that key stakeholders, namely private/public sector, seniors, caregivers, health and social service providers, long-term care homes, retirement homes, financial institutions, developers and governments (LHINs, ministries, GTA municipalities), French Language Services Planning Entities (Reflet Salvéo and Entité 4) and post-secondary educational institutions such as Collège Boréal, Glendon, UOIT, York and Schulich and University of Toronto) came together to discuss on opportunities to - create an awareness of different programs and care models within the French community - facilitate access to and expansion of French health care services and programs for Francophone adults experiencing loss of autonomy - raise funds to support the improvement of long-term care and for an eventual capital project to support building the first bilingual long-term care facility dedicated to serving Francophone adults experiencing loss of autonomy within the GTA. This one-day engagement provided an opportunity for stakeholders the opportunity to make recommendations on moving forward. As such, 13 recommendations have developed for different stakeholders including the Francophone community.

Évaluation des besoins des francophones et des Acadiens de la région de Saint-Jean pour un service de navigation - Forest, Mariève (Réseau santé en français de Terre-Neuve-et-Labrador, 2019)

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

Offering health services in French: Between obstacles and favourable factors in Anglophone hospital settings - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre de services de santé en français : entre obstacles et facteurs favorables en milieu hospitalier anglophone - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Notre chapitre vise à mettre en relief les facteurs sociaux et organisationnels qui favorisent l’offre de services de santé en français par des professionnels travaillant dans des établissements de santé majoritairement anglophones. Il présente une perspective sociologique qui invite les intervenants à tenir compte de la complexité de l’environnement socio-organisationnel dans lequel pratiquent les professionnels de la santé. Ainsi, leurs compétences linguistiques ne suffisent pas à assurer pareille offre. L’engagement de la haute direction et de ses gestionnaires, la gestion des services et des ressources humaines, les relations de travail, la disponibilité de la main-d’oeuvre bilingue, le contexte juridique et politique sont, entre autres facteurs, des éléments à considérer afin de comprendre dans tous ses aspects la prestation de services de santé en français. Plus largement, ils renvoient nécessairement aux rapports sociaux qu’entretiennent les anglophones et les francophones. Mots-clés : services de santé, environnement socio-organisationnel, droits linguistiques, professionnels de la santé.

L’offre de services de santé en français en contexte francophone minoritaire - Forgues, Éric; Bahi, Boniface; Michaud, Jacques; Deveau, Kenneth; Boudreau, Jonathan; St-Onge, Sylvain (Institut canadien de recherche sur les minorités linguistiques, 2011)

Les conditions favorables à l’établissement de services de santé pour les aînés francophones - Forgues, Éric; Couturier, Yves; Deroche, Francine (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

De l’émergence à la consolidation. L’état de santé des francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Nkolo, Christiane; Boudreau, Jonthan (Consortium national de formation en santé et Institut canadien de recherche sur les minorités linguistiques, 2009)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement de 2001 - Forgues, Éric; Landry, Rodrigue; Boudreau, Jonathan (Institut canadien de recherche sur les minorités linguistiques et Consortium national de formation en santé, 2009)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Creating a Culture of Active Offer in Both Official Languages: A Case Study of a Dialogue - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations

Vers une culture de l’offre active de services de santé dans les deux langues officielles, étude de cas d’une pratique de dialogue. - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations

Linguistic variables: A necessity for health services planning tailored to the needs of Francophones. Current Status - French Language Heatlh Services Network of Eastern Ontario (Current Status, 2012)

Réflexion sur le développement des services en matière de violence - Garceau, Marie-Luce (Reflets, 2005)

Understanding acceptability of digital health technologies among francophone-speaking communities across the world: a meta-ethnographic study - Gauthier-Beaupré, Amelie; Grosjean, Sylvie (Frontiers in Communication, 2023)
Introduction: Increasingly, people are turning toward digital health technologies to support their care management, communication with health professionals, and performing activities of daily living. Digital health technologies may be well implemented in clinical practices in several jurisdictions, but the influence of sociocultural factors may sometimes be neglected. To increase use and sustainability of these innovative solutions in health care, we need to understand acceptability among diverse groups of the population such as linguistically diverse populations. Francophone-speaking populations in Canada, for example, are known to endure challenges with income, health and difficulties associated with living in rural areas which impede on their likelihood to use digital health technologies. As part of the University of Ottawa International Francophonie Research Chair on Digital Health Technologies, this study aimed to understand the conditions that make digital health technologies acceptable among francophone-speaking communities. Methods: Using a meta-ethnography methodology, this study synthesizes international qualitative research on social acceptability of digital health technology among francophone-speaking communities. We focused on four types of digital health technologies: telemedicine, mobile technologies, wearable technologies, and robotic technologies. Using Noblit and Hare's 7 phase approach to conducting a meta-ethnography, we were able to get a comprehensive synthesis and understanding of the research landscape on the issue. Studies published between 2010 and 2020 were included and synthesized using NVivo, excel and a mind mapping technique. Results: Our coding revealed that factors of social acceptability for digital health technologies could be grouped into the following categories: care organization, self-care support, communication with care team, relational and technical risks, organizational factors, social and ethical values. Our paper discusses the themes evoked in each category and their relevance for the included digital health technologies. Discussion: In discussing the results, we present commonalities and differences in the social acceptability factors of the different digital health technologies. In addition, we demonstrate the importance of considering sociocultural diversity in the study of social acceptability for digital health technologies. Implications: The results of this study have implications for practitioners who are the instigators of digital health technology implementation with healthcare service users. By understanding factors of social acceptability among francophone-speaking communities, practitioners will be better suited to propose and support the implementation of technologies in ways that are suitable for these individuals. For policymakers, this knowledge could be used for developing policy actions based on consideration for diversity.

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Les services de santé en français pour les communautés francophones et acadiennes en situation minoritaire du Canada : bonification du schéma du CCCFSM (2001) - Giguère, Louis (Nouvelles perspectives en sciences sociales, 2013)
Nous bonifions le schéma du CCCFSM (2001) sur le développement des services de santé en français pour les communautés francophones et acadiennes en situation minoritaire (CFASM) du Canada à l’aide de données probantes recueillies lors du recensement national de 2006. Notre approche consiste à choisir, à partir d’une procédure statistique, une mesure de masse critique de francophones qui met en évidence un schème cohérent d’offre et de demande de services de santé sur une base géographique juridictionnelle. L’offre et la demande sont plus grandes là où la vitalité linguistique des CFASM est plus grande. Dans l’ensemble, l’offre tombe en deçà de la demande; ceci suggère une demande latente de services en français et est consistant avec les études d’offre active des services en français dans les CFASM. Nos résultats sont aussi consistants avec les trois phases évolutives de sensibilisation, de structuration et de consolidation proposées par le CCCFSM (2001). Nous discutons des limitations méthodologiques et en tirons des leçons pour les réseaux de santé francophones des CFASM. Mots-clés : CFASM, CLOSM, communauté francophone, minoritaire, vitalité linguistique, langues officielles, réseaux de santé, services en français, offre et demande

Validation d’un schème national sur le développement des services de santé pour les communautés francophones et acadiennes en situation minoritaire au Canada : arrimage à des assises théoriques et modélisation - Giguère, Louis (Nouvelles perspectives en sciences sociales, 2014)
Nous avons présenté (Giguère, 2013), pour les communautés francophones hors Québec (CFASM), un schème juridictionnel national qui illustre l’offre et la demande de services de santé en français en fonction d’une masse critique de francophones qui reflète la vitalité linguistique de ces communautés. Nous corroborons ce schème à l’aide de procédures statistiques dont l’une identifie une forte association entre le rapport offre/demande (un ratio) et des facteurs qui reflètent la cohérence linguistique et culturelle des deux communautés de langue officielle. Ce résultat est cohérent avec le cadre de vitalité linguistique déjà proposé (Giguère, 2013), et il fait écho au travail de terrain de Forgues, Bahi et Michaud (2011) et aux modèles psycho-langagiers et d’autonomie culturelle de Deveau, Landry et Allard (2009), de Landry, Allard et Deveau (2007, 2008) et de Landry (2012). Nous modélisons le développement des services de santé en français pour les CFASM dans un cadre national structurant qui est cohérent avec ces assises empiriques et théoriques. Cette modélisation suggère deux approches stratégiques distinctes mais complémentaires pour favoriser le développement des services de santé en français. Mots-clés : CFASM, communauté francophone, minoritaire, développement communautaire, vitalité langagière, réseautage, schéma CCCFSM, assises théoriques, modélisation en diagramme de phase

Le potentiel d'offre et de demande de Services médicaux et diagnostiques dans la langue de communautés minoritaires : où se situe le français en Colombie-Britannique? - Giguère, Louis; Conway, Brian (Reflets, 2014)
Une étude comparative du potentiel de services médicaux dans les langues minoritaires de Colombie-Britannique révèle que des médecins non-francophones parlant français génèrent une retombée linguistique qui amplifie l’offre potentielle de services de santé et de services sociaux en français de façon dramatique. Ce mécanisme structurant s’appliquerait aux autres professions de la santé et des services sociaux, partout au Canada et il serait plus prononcé plus le contexte est minoritaire. Les communautés francophones doivent faire plus pour identifier, engager et outiller les professionnels et professionnelles « francophiles » et elles doivent élaborer une logique d’équité innovatrice pour dégager le potentiel d’offre de services de santé et de services sociaux en français dans un contexte multilingue. Mots-clés : CFASM, CLOSM, médecins parlant français, minorités linguistiques, équité, services d’interprétation, offre et demande

L’ambition territoriale dans le dossier de la santé en français - Gilbert, Anne; Lefebvre, Marie; Bouchard, Louise (Francophonies d’Amérique, 2010)
Dix ans se sont écoulés depuis le jugement Montfort, qui consacrait l’Hôpital comme une composante essentielle de la vitalité des communautés francophones en situation minoritaire. Jusqu’à quel point cette reconnaissance du droit à un service en français, accessible dans des établissements localisés dans les milieux dans lesquels la minorité évolue, a-t-elle mené à une ambition plus territoriale chez les intervenants francophones ? L’analyse des propos tenus par 38 participants à un exercice de cartographie conceptuelle sur l’avenir des services de santé en français en Ontario révèle qu’ils ne s’aventurent pas très loin sur le terrain des modalités de l’édification d’un véritable territoire francophone en santé. L’institution est évoquée, mais davantage comme un projet appartenant à un horizon lointain que comme un enjeu actuel. En guise de conclusion, les auteures se sont interrogées sur les effets d’une telle vision sur l’avenir des services de santé en français.

La pratique de la physiothérapie en milieu minoritaire : mon expérience en tant que francophone à l’Hôpital de Hamilton - Goulet, Anik (Reflets, 2002)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement. Mise à jour : recensement de 2011 - Guignard-Noël, Josée; Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques, 2014)

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Étude de référence sur les services bilingues au sein des établissements de santé canadiens - Guignard Noël, Josée; LeBlanc, Joannie; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Frontières linguistiques et culturelles : le cas de l’accessibilité aux services de santé et de services sociaux pour la population anglophone de la région de Québec - Hanrahan, Louis; Cloutier, Annabelle; Walling, Richard (Cahiers de l’ÉDIQ, 2016)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance

Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais.

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Les priorités de recherche sur la santé des francophones en Ontario - Kalay, Anifa L.; Chomienne, Marie-Hélène; Farmanova, Elina (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux, 2019)

Actes du colloque : l'offre active des services sociaux et de santé en français - La Cité universitaire francophone, Université de Régina; Consortium national de formation en santé (Colloque offre active symposium, 2019)

La nécessité des tests normalisés pour l’évaluation orthophonique et audiologique des jeunes francophones vivant en situation linguistique minoritaire : mythe ou réalité? - Lagacé, Josée; Lefebvre, Pascal (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
La plupart des enfants francophones vivant en situation linguistique minoritaire au Canada sont bilingues. Les audiologistes et les orthophonistes qui effectuent des évaluations pour déterminer si ces derniers présentent des troubles de la communication revendiquent l’élaboration de tests normalisés pour cette population. Pourtant, les pratiques exemplaires proposent des moyens plus efficaces pour déterminer la présence d’un trouble de la communication auprès des enfants bilingues. Ce chapitre recense les données des écrits scientifiques et présente de nouvelles données de recherche démontrant l’écart entre les pratiques exemplaires et les pratiques actuelles liées à l’utilisation de tests normalisés auprès des enfants bilingues en audiologie et en orthophonie. Afin d’améliorer les services pour ces enfants, des recommandations sont formulées pour les programmes universitaires, les programmes de formation continue, les employeurs et les parents. Mots-clés : tests standardisés, tests normalisés, bilinguisme, audiologie, orthophonie, pratiques exemplaires

The necessity for normalized tests for speech, language, and hearing assessment of young Francophone children living in linguistic minority settings: Myth or reality? - Lagacé, Josée; Lefebvre, Pascal (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)

Manque de collaboration, manque d'effectifs ou disparition des données : le nécessaire et difficile accès aux archives psychiatriques - LeBel, Marie (Santé mentale au Québec, 2016)
L’article présente comment, dans le cadre d’une recherche sociohistorique sur les soins et services en santé mentale dans les communautés de langue officielle en situation minoritaire, la question des sources et de l’accès aux archives est cruciale. Dans le cas d’une telle étude, le matériau le plus évidemment susceptible de témoigner des soins reçus, des transferts du patient d’un lieu à un autre et d’un spécialiste à un autre est le document d’archives hospitalières. Et, puisque notre recherche s’intéresse aux itinéraires suivis par les patientes et patients en fonction des diagnostics posés et des traitements proposés, on comprendra toute l’importance que peut représenter l’accès aux archives psychiatriques, incluant les dossiers patients, les sommaires d’admission, les documents de fondation, les projets de restructuration consécutifs aux recommandations politiques, etc. Mots-clés : histoire de la médecine, minorités et santé, histoire de la santé mentale, archives psychiatriques, santé mentale et francophonie

Peut-on parler d'une déshospitalisation des services ? Les soins en santé mentale de la minorité de langue officielle dans le Nord-Est ontarien - LeBel, Marie (La fin de l'asile ? Histoire de la déshospitalisation psychiatrique dans l'espace francophone au xxe siècle, 2018)

Pour un système de santé en français amélioré au Nouveau-Brunswick - Leblanc, Gino (Gouvernement du Nouveau-Brunswick, 2010)

Toward an improved health system in french in New Brunswick - Leblanc, Gino (New-Brunswick Government, 2010)

La bilinguisation des services de santé et des services sociaux du Québec - Lefebvre, Mathilde (Institut de recherche en économie contemporaine, 2014)

Identité, culture et représentations de la santé et des maladies - Lévesque, Annabel (Cahiers franco-canadiens de l’Ouest, 2015)
La santé et les maladies représentent des concepts subjectifs qui varient en fonction de nombreux facteurs, notamment la culture d’appartenance. Étant donné le contexte multiculturel canadien, il importe de considérer le contact interculturel lorsqu’on s’interroge au sujet des représentations de la santé et des maladies chez les groupes minoritaires puisque ces derniers sont soumis à l’influence d’autres cultures, dont la culture du groupe dominant. Ainsi, le degré d’identification à la culture d’origine et à la culture dominante détermine les représentations auxquelles souscrivent les individus issus d’un groupe minoritaire. Chez ceux qui s’identifient à leur culture d’origine, on note un lien entre leur état de santé et la vitalité culturelle et linguistique de leur communauté. Les efforts visant à promouvoir la santé et le bien-être de ces individus devraient donc être axés sur le maintien de leur héritage culturel et linguistique. Les professionnels de la santé, pour leur part, devraient engager le dialogue avec leurs patients au sujet de leurs représentations culturelles de la santé et des maladies, et ce, dans un climat empreint de respect. Cette pratique pourrait contribuer à la satisfaction des patients avec les soins reçus et, par le fait même, à l’adoption de comportements sains.

Identité ethnolinguistique, continuité cultuelle et santé mentale chez les jeunes franco-manitobains : une analyse exploratoire - Levesque, Annabel; de Moissac, Danielle (Minorités linguistiques et société, 2018)
L’objectif de cette étude était d’explorer divers profils identitaires collectifs auprès des étudiants universitaires franco-manitobains, et ce, à partir du sentiment d’appartenance à la communauté franco-manitobaine et de la perception de continuité ethnolinguistique. Quinze répondantes et répondants ont participé à une entrevue individuelle. Quatre profils identitaires collectifs ont émergé : optimiste, en changement, inquiet et indifférent-désengagé. La mise en relation des catégories thématiques a permis d’émettre certaines hypothèses : a) Le profil identitaire des répondants serait fonction des rapports qu’ils entretiennent avec les exogroupes majoritaires ainsi que des structures et rapports sociaux au sein de l’endogroupe. b) Ces profils seraient, en retour, liés à la santé mentale des répondants ; ceux au profil inquiet semblent démontrer un bienêtre psychologique moindre comparativement aux autres répondants. c) Les profils identitaires collectifs orienteraient le recours aux services de soutien formels et informels ; la majorité des répondants, à l’exception de ceux au profil indifférent-désengagé, dit préférer recevoir de l’aide en français. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Reference framework: Training for active offer of French-language health services - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Les soins de santé en français à l'extérieur du Québec - Marmen, L.ouise; Delisle, Sylvain (2003)

Language and culture in the caregiving of people with dementia in care homes - What are the implications for well-being? A scoping review with a Welsh perspective - Martin, Conor; Woods, Bob; Williams, Siôn (Journal of Cross-Cultural Gerontology, 2019)
The loss of language skills is one of the most challenging aspects of living with dementia. This is particularly true for bilingual individuals, who have difficulty in maintaining fluency in more than one language. Language and culture overlap greatly, with potential implications for the well-being of people with dementia (PWD) being cared for in their ‘second’ language or culture. Our aim was to review the available relevant literature, together with an examination of the potential effects of linguistic incongruity on healthcare in general for Welsh speakers in Wales. A literature search yielded 50 articles, which were analysed using the scoping review methodological framework. We found that the presence of cultural and linguistic congruity was beneficial for PWD living in care homes, and that their absence was detrimental. The absence of linguistic congruity is a strong predictor for decreased well-being in people in such settings, due to communication barriers between residents and carers, which result mainly from the loss of PWD’s second language skills. Such barriers may lead to inappropriate care, e.g. being unable to obtain help to self-care, as well as social isolation. This review suggests that strategies need to be developed across the world to accommodate bilingual individuals requiring a care home for their dementia needs. There is a particular dearth of research regarding the influence of bilingualism on the experience of dementia care in those areas of the UK where the indigenous population are most likely to be bilingual (i.e. parts of Wales).

Soins de longue durée en français. Rapport final - McQuaid, Steve (The Atlantic Evaluation Group Inc, 2010)

La prise en compte du français dans l’organisation des services en foyers de soins majoritairement anglophones au Canada - Michaud, Jacques; Forgues, Éric; Guignard Noël, Josée (Minorités linguistiques et société, 2015)
L’accès aux services de santé en français préoccupe grandement les communautés francophones vivant en situation minoritaire. Le présent article offre un survol de l’espace francophone dans les résidences collectives d’aînés du Nouveau-Brunswick, de la Nouvelle-Écosse et de l’Ontario à la lumière d’une recherche exploratoire menée en 2012. L’analyse des données obtenues auprès d’aînés, d’aidants et du personnel, l’examen de la répartition géographique des résidences et de la population d’aînés francophones, ainsi qu’un aperçu du contexte réglementaire encadrant le fonctionnement de ces résidences permettent de définir la problématique pertinente. Des actions en vue d’améliorer la situation sont examinées. Mots-clés : espace francophone, services de santé en français, francophones en situation minoritaire, foyers de soins, résidences collectives, vieillissement de la population

Pratique # 20 : Talking About Mental Illness (TAMI) en français (Territoires du Nord-Ouest) - Michel, Jean Nephetaly; van Kemenade, Solange; Benoît, Josée (2021)

Guide pour l’élaboration du programme d’accès aux services de santé et aux services sociaux en langue anglaise - Ministère de la santé et des services sociaux (2018)

The Basque paradigm shift: From legislative language policies to person-centred care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation. Keywords: patient-centred care, bilingual pathways, language appropriate care, preferred language, active offer

Enabling the participation of marginalized populations: Case studies from a health service organization in Ontario, Canada - Montesanti, Stephanie. R.; Abelson, Julia; Lavis, John. N.; Dunn, James. R. (Health Promotion International, 2017)
We examined efforts to engage marginalized populations in Ontario Community Health Centers (CHCs), which are primary health care organizations serving 74 high-risk communities. Qualitative case studies of community participation in four Ontario CHCs were carried out through key informant interviews with CHC staff to identify: (i) the approaches, strategies and methods used in participation initiatives aimed specifically at engaging marginalized populations in the planning of and decision making for health services; and (ii) the challenges and enablers for engaging these populations. The marginalized populations involved in the community participation initiatives studied included Low-German Speaking Mennonites in a rural town, newcomer immigrants and refugees in an urban downtown city, immigrant and francophone seniors in an inner city and refugee women in an inner city. Our analysis revealed that enabling the participation of marginalized populations requires CHCs to attend to the barriers experienced by marginalized populations that constrain their participation. Key informants outlined the features of a ‘community development approach’ that they rely on to address the barriers to marginalized peoples' involvement by strengthening their skills, abilities and leadership in capacity-building activities. The community development approach also shaped the participation methods that were used in the engagement process of CHCs. However, key informants also described the challenges of applying this approach, influenced by the cultural values of some groups, which shaped their willingness and motivation to participate. This study provides further insight into the approach, strategies and methods used in the engagement process to enable the participation of marginalized populations, which may be transferable to other health services settings.

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

La santé mentale des jeunes en contexte linguistique minoritaire : une étude pilote sur la configuration de l'offre de services en français dans la région sociosanitaire de Winnipeg - Ndiaye, Léna Diamé; Sombié, Guipinhali Nathalie (Minorités linguistiques et société, 2018)
Dans cet article, nous présentons une étude qui visait à cerner la configuration actuelle des services de santé mentale offerts aux jeunes francophones de la région sociosanitaire de Winnipeg et à déterminer le degré d’articulation entre les dispositifs institutionnels et non institutionnels de prise en charge. Une grille d’entrevue semi-structurée a permis de recueillir des données auprès de 15 répondants provenant des organismes de la région sociosanitaire de Winnipeg. Les résultats de l’étude indiquent qu’un nombre très limité d’organismes offre des services de santé mentale en français aux jeunes francophones. L’analyse nous a également montré que la plupart de ces organismes n’entretiennent pas des relations de complémentarité entre eux, mais sont régis par une circularité relationnelle fondée sur des services ponctuels à travers une dualité formelle-informelle. Mots-clés : santé mentale, jeunes, offre de services, accessibilité, contexte linguistique minoritaire

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

L’offre active de services en français : généalogie d’un outil de politique publique - Normand, Martin (Francophonies d'Amérique, 2019)
L’offre active de services en français est un principe qui s’est rapidement imposé dans le discours des principaux intervenants dans le domaine de la promotion et de la protection des langues officielles et de la dualité linguistique au Canada. Elle a été intégrée à des politiques, à des règlements et à des lois au palier fédéral et dans plusieurs provinces canadiennes. Plusieurs travaux ont été consacrés aux aspects liés à la mise en oeuvre du principe. Cet article va au-delà de ces contributions pour retracer l’histoire de l’offre active. Il répond à deux questions : 1) quelle est l’origine de l’offre active ? et 2) quels sont les principaux jalons dans son évolution et sa diffusion ? L’hypothèse est que les représentations initiales de l’offre active n’étaient pas que techniques ou formalistes et qu’elles se sont effritées avec le temps. La recherche repose essentiellement sur des sources primaires et secondaires, qui nous ont permis de reculer jusqu’au moment où le principe semble avoir émergé. Le texte s’organise autour de trois périodes : la conceptualisation, l’institutionnalisation et la diffusion de l’offre active.

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)

Adaptation linguistique des soins et des services de santé : enjeux et stratégies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Language adaptation in health care and health services: Issues and strategies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Les femmes aidantes naturelles dans les communautés francophones et acadienne du Canada. Sommaire - Ouimette, Johanne; Miron, Isabelle. N (Alliance des femmes de la francophonie canadienne, 2006)

Aînés francophones et intervenants multiethniques en santé : un projet de formation interculturelle adapté aux collègues francophones canadiens - Parent, R.; Bouchard, Louise; Lebel, M. (Reflets, 2014)

Le laboratoire d’idées ad hoc et le développement de partenariats communautaires dans les services de santé - Parent, Roger (Minorités linguistiques et société, 2015)
Cet article fait état d’une recension des écrits effectuée pour le Consortium national de formation en santé (CNFS) autour du phénomène des laboratoires d’idées ou think tanks. Cette recension visait à identifier la forme de laboratoire d’idées en mesure de favoriser la prestation de soins de santé linguistiquement et culturellement appropriés dans les communautés d’expression française du Canada. Les écrits recensés font état de l’évolution du think tank classique vers des communautés de recherche axées sur un virage pragmatique qui redéfinit le savoir universitaire en fonction des besoins des usagers. Les pratiques transformatrices liées à cette démocratisation du savoir innovent en raison de leurs approches systémiques et organisationnelles envers la résolution de problèmes culturels. Mots-clés : laboratoire d’idées, communauté, santé, culture, système

Francophone patients - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Patientèle francophone - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Hôpital Montfort : reflets de la francophonie en évolution - Perron Roach, Daniel (Reflets, 2015)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Des nôtres : une analyse des besoins des personnes LGBTQ2S d’expression française du Manitoba - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya (Collectif LGBTQ du Manitoba et Université de Saint-Boniface, 2021)
Cette étude, menée sous l’impulsion du Collectif LGBTQ* du Manitoba, est la première à sonder les besoins de la communauté LGBTQ2S d’expression française au Manitoba (désormais la « Communauté »). L’objectif était de brosser le portrait de la situation actuelle de ses membres de 18 ans et plus quant à 1) leur profil sociodémographique et ethnoculturel; 2) leurs besoins en matière de soutiens sociaux et de soins de santé; 3) leurs perceptions de discrimination ou de stigmatisation, tant par rapport à la langue qu’à l’orientation sexuelle et/ou à l’identité de genre; et 4) leurs priorités pour l’avenir. Par l’entremise d’un sondage en ligne, la Communauté a su nous informer de ses besoins prioritaires, particulièrement en matière de santé mentale et de soutien social.

Ciel éclairci ! Vers un meilleur accès aux services de santé mentale et de lutte contre les dépendances en français en Ontario - Programme de soutien au système provincial (Centre de toxicomanie et de santé mentale, 2018)

The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Rhodes, Emily; Guerin, Eva; Carson, Sarah; Prud’homme, Denis; Tanuseputro, Peter (BMC Health Services Research, 2020)
Background Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a language-discordant hospital is a risk factor for in-hospital harm. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2007 to 2015) who were admitted to a hospital in Eastern or North-Eastern Ontario, Canada. Patient language (obtained from home care assessments) was coded as English (Anglophone group), French (Francophone group), or other (Allophone group); hospital language (English or bilingual) was obtained using language designation status according to the French Language Services Act. We identified in-hospital harmful events using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results The proportion of hospitalizations with at least 1 harmful event was greater for Allophones (7.63%) than for Anglophones (6.29%, p <  0.001) and Francophones (6.15%, p <  0.001). Overall, Allophones admitted to hospitals required by law to provide services in both French and English (bilingual hospitals) had the highest rate of harm (9.16%), while Francophones admitted to these same hospitals had the lowest rate of harm (5.93%). In the unadjusted analysis, Francophones were less likely to experience harm in bilingual hospitals than in hospitals that were not required by law to provide services in French (English-speaking hospitals) (RR = 0.88, p = 0.048); the opposite was true for Anglophones and Allophones, who were more likely to experience harm in bilingual hospitals (RR = 1.17, p <  0.001 and RR = 1.41, p <  0.001, respectively). The risk of harm was not significant in the adjusted analysis. Conclusions Home care recipients residing in Eastern and North-Eastern Ontario were more likely to experience harm in language-discordant hospitals, but the risk of harm did not persist after adjusting for confounding variables.

Cognitive health initiative for Francophone seniors in the GTA - Reflet Salvéo; Entité 4 (Options fo Service Models, 2017)

Énoncé de position commune sur la variable linguistique - Regroupement des Entités de planification des services de santé en français de l’Ontario (Réseau des services de santé en français de l’Est de l’Ontario, 2013)

Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire( infographie) - Réseau communautaire de santé et de services sociaux/Community Health and Social Services Network (2019)

La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés - Réseau des services de santé en français de l'Est de l'Ontario (2022)

Les variables linguistiques : un impératif pour une planification de services de santé adaptée aux besoins des francophones. État des lieux - Réseau des services de santé en français de l’Est de l’Ontario (État des lieux, 2012)

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)

Recommandation du Réseau. Collecte des données linguistiques - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Les réseaux : architectes de la santé en français - Réseau des services de santé en français de l’Est de l’Ontario; Réseau de santé en français du Moyen-Nord de l’Ontario; Réseau francophone de santé du Nord de l’Ontario; Réseau franco-santé du Sud de l’Ontario (Les réseaux : architectes de la santé en français, 2007)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Préparer le terrain : soins de santé primaires en français en Ontario. Rapport provincial - Réseau francophone de santé du Nord de l’Ontario; Réseau de santé en français du Moyen-Nord de l’Ontario; Réseau franco-santé du Sud de l’Ontario; Réseau des services de santé en français de l’Est de l’Ontario (2006)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Santé mentale en français. Comprendre les enjeux et l’urgence de collaborer aux TNO - Réseau TNO Santé (Comprendre les enjeux et l’urgence de collaborer aux TNO, 2018)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine - Richardson, Mary (2019)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Anglophone Magdalen Islanders, 2018)

Implementing the Evidence for Language-appropriate Health Care Systems: The Welsh Context - Roberts, Gwerfyl W.; Burton, Christopher R. (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Like Canada, Wales, UK is a bilingual nation: the Welsh language is an important part of its national identity and legislative framework. This has implications for the delivery of public sector services, particularly in the context of health and social care, where responding to the language needs of service users is fundamental to quality health care provision. Nevertheless, despite the strengthening policy commitment for a whole-system approach towards enhancing Welsh language services, there is a paucity of evidence to guide best practice in organizational planning in health care settings. This commentary outlines the context and significance of bilingual health care provision in Wales and the implications for building and embedding the evidence base. It calls for further work to translate our knowledge and understanding of language-appropriate practice to provide more effective and sensitive health care services; and to close the implementation gap between evidence and practice. Given the relevance of this challenge for health care providers in Canada who plan and deliver services for French-language minorities, this approach has resonance across our research communities. Thus, in our common pursuit to establish integrated knowledge translation research for language-appropriate health care systems, this commentary offers a focus for reflection, discussion and collaborative action. KEY WORDS: Knowledge management; language; minority health; organizational change; Wales

The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region - Sanderson, Duncan; Grégoire, Louise; Reinharz, Daniel (Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique, 2006)

Le Centre de santé de Clare : un modèle pour l'accès à des services de santé en français - Sangaré, Yalla (Reflets, 2014)

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Implementing Active Offer of Services in Both Official Languages in a Hospital Setting in Ontario - Sauvé-Schenk, Katrine; Savard, Jacinthe; Durand, François (Healthcare Policy, 2024)
Providing services in a patient's preferred language is linked to safe and quality care. This paper presents the process and outcomes of implementing practices of active offer (AO) of French-language services in a hospital setting in a region of Ontario with a low density of francophones. Participating unit managers and site coordinators selected AO practices and carried out an implementation plan. The implementation's success was linked to the support received from higher management and site coordinators. Challenges included the managers' rival priorities and perceived language priorities. This process could be applied to meet the needs of other language communities.

Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français - Sauvé-Schenk, Katrine; Savard, Jacinthe; Prud’homme, Denis; Durand (Chiocchio), F.; Delluc, C. (Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Évaluation métrologique de la Mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Benoît, Josée; Bouchard, Pier (Reflets, 2014)
Comment peut-on mesurer l’impact des actions entreprises pour améliorer l’offre active de services sociaux et de santé en français dans les communautés francophones en situation minoritaire? Un questionnaire mesurant premièrement les comportements individuels de l’offre active et deuxièmement la perception du soutien organisationnel à faire de l’offre active a été créé. La validité de contenu de la Mesure de l’offre active de services en françaisen contexte minoritaire a été établie à l’aide d’une recension d’écrits, de consultations menées auprès d’expertes et d’experts et d’un sondage Delphi pancanadien. Sa fidélité a été examinée à partir de données recueillies auprès de récents diplômés en santé et en service social. L’outil démontre une bonne consistance interne et des études auprès d’un plus large échantillon sont nécessaires pour augmenter la confiance envers sa stabilité temporelle. Il s’agit des premiers pas d’une démarche visant à mesurer l’évolution des comportements d’offre active à la suite d’activités de formation ou de changements organisationnels en faveur de services en français. Une telle mesure est aussi susceptible d’être utile dans les recherches visant à saisir les déterminants de ces comportements d’offre active. Mots-clés : Offre active de services en français, formation des professionnelles ou professionnels en santé et services sociaux, soutien organisationnel, évaluation, minorité, langue et services, qualité des soins et services, sécurité des clientes ou clients/patientes ou patients

Behaviours demonstrating active offer: Identification, measurement, and determinants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Les comportements favorables à l’offre active, leur mesure et leurs déterminants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, nous présenterons comment nous avons répertorié des comportements favorables à une offre active (OA) de services sociaux et de santé en français en contexte minoritaire, comment nous les avons mesurés et comment nous avons utilisé ces mesures pour déceler des déterminants de l’OA. Nous présentons en détail l’élaboration des outils qui ont servi à mesurer les comportements d’OA, le soutien organisationnel perçu envers l’OA et les caractéristiques personnelles qui peuvent influer sur les comportements d’OA (déterminants). Diverses méthodes quantitatives ont été utilisées pour atteindre ces objectifs. Les résultats obtenus démontrent la présence d’un fort lien entre le soutien organisationnel perçu et les comportements individuels d’OA. À soutien organisationnel égal, les caractéristiques individuelles associées à une plus grande propension à démontrer des comportements d’OA incluent une formation sur l’OA, l’affirmation identitaire et la compétence en français. Le sentiment de compétence en anglais est quant à lui associé négativement aux comportements individuels d’OA de services en français. Une meilleure connaissance de ces déterminants permet de raffiner les stratégies de sensibilisation et d’éducation des futurs professionnels de la santé et des services sociaux envers l’OA. Mots-clés : comportements d’offre active, mesure, déterminants, soutien organisationnel, comportements individuels, recherche quantitative.

Conception d’outils de mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée; Drolet, Marie; Dubouloz Claire-Jehanne (Minorités linguistiques et société, 2015)
Dans les communautés francophones en situation minoritaire, le besoin d’une offre active des services en français, plutôt que d’un service qui suit la demande, est de plus en plus reconnu. Les professionnels en santé et en service social doivent être formés à cette approche et les résultats devront être évalués. Cet article décrit le processus de création et de validation de contenu (recension d’écrits, consultations d’experts, sondage Delphi pancanadien) de deux questionnaires portant sur les comportements caractéristiques de l’offre active de services sociaux et de santé en français : le premier mesurant les comportements individuels d’offre active des intervenants et le deuxième mesurant la perception de ces derniers du soutien organisationnel à l’offre active. Mots-clés : offre active, formation des professionnels de la santé et des services sociaux, évaluation, minorités, langue et services, soutien organisationnel

Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire - Savard, Jacinthe; Savard, Sébastien; Drolet, Marie; De Moissac, Danielle; Kubina, Lucy-Ann; van Kemenade, Solange; Benoit, Josée; Couturier, Yves (2017)

Framework for the Analysis of Health and Social Services Access and Integration for Official Language Minority Communities - Savard, Jacinthe; Savard, Sébastien; Drolet, Marie; De Moissac, Danielle; Kubina, Lucy-Ann; van Kemenade, Solange; Benoit, Josée; Couturier, Yves (2018)

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 1 : Le Guide de mise en œuvre du mandat linguistique d’Actionmarguerite (Manitoba). - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 11 : The Information and Support Guide for Caregivers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 2 : Une maisonnée francophone au Foyer Summerset (Île-du- Prince-Édouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

Contributions d’OZi à l’état des lieux des services de santé en français en Ontario. - Scullion, David; Taillon, Myriam; Ranger, Marie-Christine; Glaude, Normand; Desaulniers, Jacinthe (Minorités linguistiques et société, 2024)
Entre 2017 et 2020, l’organisme OZi a effectué la collecte et l’analyse de données sur les services de santé en français à l’échelle de la province, dans le cadre de la Loi sur les services en français de l’Ontario. Les résultats de cette recherche descriptive et exploratoire portent sur la répartition géographique de l’offre des services de santé en français, le continuum de soins, les exigences de la désignation et les ressources humaines possédant des capacités linguistiques en français. Ces résultats permettent de dresser l’état des lieux des services de santé en français en Ontario, en mettant en lumière les points forts comme les lacunes des services de santé en français. Les résultats sont discutés sous l’angle de l’accès et la planification des services de santé en français ainsi que celui de la performance de la désignation. Mots-clés : santé, offre active, Ontario, désignation des fournisseurs de santé, continuum de soins

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Le renforcement des capacités : déclin ou levier à l'amélioration de la qualité de vie des aînés ? Le cas de St-Wilfred et de Robertville en Acadie - Simard, Majella (Reflets, 2022)
Le vieillissement de la population représente une réalité complexe. Bien que les causes attribuables à ce phénomène fassent consensus auprès des chercheurs, ses manifestations et ses conséquences diffèrent d’un endroit à l’autre. Dès lors, le rythme et l’intensité du vieillissement ainsi que les moyens déployés par les différents acteurs sociaux pour en atténuer les effets et améliorer les conditions de vie des aînés se manifestent aussi différemment selon les milieux géographiques. Pour diverses raisons liées à la démographie et à la géographie, les défis liés à la gestion du vieillissement tendent à se manifester avec plus d’acuité en milieu minoritaire francophone. L’objectif de cet article consiste à examiner la contribution du modèle de renforcement des capacités à l’amélioration de la qualité de vie des aînés vivant au sein de deux localités sises en milieu rural minoritaire francophone. L’étude de cas exploratoire couplée à l’approche des représentations sociales des acteurs a été retenue comme méthode d’analyse. Des entrevues semi-dirigées effectuées auprès d’intervenants locaux et communautaires ainsi que la tenue de deux groupes de discussion constituent les instruments d’analyse qui ont été mobilisés. Bien que les résultats de notre analyse révèlent le rôle d’avant-plan de la résilience, du réseautage, de la vie relationnelle, du sentiment identitaire et du capital social dans l’amélioration de la qualité de vie des aînés, ces composantes relatives à leurs facultés s’avéreraient insuffisantes afin de favoriser un vieillissement sur place, d’où la nécessité de déployer en amont une politique territoriale du vieillissement. Mots-clés : vieillissement, milieu rural, renforcement des capacités, qualité de vie, Acadie

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Améliorer l’accès des personnes âgées du Manitoba et de l’Île-du-Prince-Édouard aux services de santé en français - Société Santé en français (2014)

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)

Mémoire sur l’accès aux soins de santé primaires au Nouveau-Brunswick - Société Santé et Mieux-être en français du Nouveau-Brunswick; Mouvement Acadien des Communautés en Santé du Nouveau-Brunswick Inc (2011)

L’offre de services dans les deux langues officielles dans le domaine de la santé : à nous d’y voir ! - Société Santé et Mieux-être en français du Nouveau-Brunswick; Réseau-action formation et recherche (2009)

La thérapie informatisée : une option pouvant faciliter l'accès à la thérapie chez les jeunes adultes ? - Talbot, France; LeBlanc, Josée; Jbilou, Jalila (Santé mentale au Quebec, 2015)
Introduction Les jeunes adultes ont, au Canada, les plus hauts taux de prévalence de l’anxiété et de la dépression, et sont aussi ceux qui utilisent le moins les services traditionnels de santé mentale. Faciliter l’accès à la thérapie chez les jeunes est ainsi particulièrement important, et ce, encore davantage dans les régions canadiennes plus rurales et auprès des minorités linguistiques. La thérapie informatisée pourrait être une option. Objectifs Cette étude vise à évaluer jusqu’à quel point l’autostigmatisation, un besoin d’autonomie et les attitudes face à la thérapie informatisée permettent de prédire l’intention d’utiliser cette thérapie chez de jeunes adultes francophones. L’impact de la visite du site Web d’une clinique virtuelle sur cette intention a également été évalué. Méthode Quarante-quatre étudiants fréquentant une université francophone du Nouveau-Brunswick ont complété, en ligne, des mesures autorapportées avant et suite à la visite du site Web de la clinique virtuelle MindSpot, en Australie, qui offre des thérapies informatisées. Résultats Une séquence de corrélations significatives entre les variables étudiées est observée, mais seules des attitudes plus positives à l’égard de la thérapie informatisée sont directement corrélées à une plus grande intention de l’utiliser. La visite du site Web a produit une augmentation significative et importante de l’intention d’utiliser la thérapie informatisée. Conclusions La thérapie informatisée pourrait faciliter l’accès aux traitements fondés sur les données probantes du stress, de l’anxiété et de la dépression chez les jeunes adultes francophones du Nouveau-Brunswick, voir d’autres parties du Canada. Cette approche demeure peu répandue encore à travers le pays. Mots-clés : thérapie autogérée, thérapie informatisée, jeunes adultes, anxiété, dépression, attitudes

La satisfaction des patients francophones de l’Est de l’Ontario traités en réadaptation à domicile - Tardif, Charles; Dallaire, Christine (Francophonies d’Amérique, 2010)
L’accès à des services de santé en français est aujourd’hui une des revendications importantes des porte-drapeaux francophones non seulement pour assurer la santé individuelle des francophones mais aussi pour favoriser la vitalité des communautés. Cependant, certains des francophones qui font appel aux soins ou à l’appui des professionnels de la santé demandent des services en français, alors que d’autres sont satisfaits de recevoir des services en anglais. Cette étude s’inspire de l’analyse des discours développée par Michel Foucault pour examiner les discours que reproduisent les francophones qui reçoivent des soins de réadaptation à domicile, en français et/ou en anglais. Des entrevues semi-dirigées ont été effectuées avec 12 patients francophones dans l’Est de l’Ontario. Les participants de l’étude sont de façon générale satisfaits des soins reçus, mais la langue des services ne répond pas nécessairement à leurs attentes. Ce sont évidemment ceux qui ne peuvent s’exprimer en anglais, d’une part, et ceux qui s’affichent fièrement comme francophones, d’autre part, qui préfèrent recevoir des soins en français. Toutefois, ce ne sont pas que les caractéristiques linguistiques et identitaires des patients qui influencent les critères qu’ils jugent prioritaires pour évaluer les soins reçus. En effet, leur façon de concevoir leur rapport vis-à-vis le professionnel de la santé joue aussi sur l’importance qu’ils accordent à la langue des soins.

Joint Position Statement on the Active Offer of French Language Health Services in Ontario - The Regroupement des Entités de planification des services; de santé en français de l’Ontario; and; the Alliance des Réseaux ontariens de santé en français (2015)

Maintien à domicile : capacité d’offre de services communautaires actuels et futurs au Nouveau-Brunswick - Thériault, Danielle; Dupuis-Blanchard, Suzanne (Service Social, 2017)
La présente étude comporte trois objectifs : 1) déterminer l’état actuel des services offerts pour le maintien à domicile; 2) explorer la nature de la planification des services futurs pour le maintien à domicile; et 3) exposer les défis reliés aux services et les moyens qui s’offrent aux organismes pour que les services répondent le plus efficacement possible aux besoins des personnes âgées francophones. De type séquentiel exploratoire mixte, cette étude a permis de recueillir des données qualitatives pour bonifier des résultats quantitatifs. Quarante-neuf gestionnaires ont répondu au questionnaire en ligne et 11 entrevues ont été réalisées. Huit thèmes communs ont été dégagés en lien avec les objectifs, thèmes qui montrent une préoccupation pour la viabilité des services communautaires en maintien à domicile. Mots-clés : personnes âgées, maintien à domicile, planification, gestion, organismes communautaires, francophones

Désinstitutionalisation psychiatrique en Acadie, en Ontario francophone et au Québec, 1930-2013 - Thifault, Marie-Claude; Dorvil, Henri (Presses de l’Université du Québec, 2015)

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

La réadaptation : son visage français en Ontario [numéro thématique] - Tremblay, Louis E. (Reflets, 2002)

Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français et Santé Canada, 2012)

Study on linguistically and culturally adapted healths services: A pan-Canadian portrait - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français & Health Canada, 2012)

L’infirmière psychiatrique, leader de l’équipe multidisciplinaire : étude de cas, Hôpital Montfort, 1976-2002 - Valentina Moya, Silvia. Maria (L’infirmière psychiatrique, leader de l’équipe multidisciplinaire : étude de cas, Hôpital Montfort, 2018)
Cet article a pour but de présenter l’espace relationnel de l’infirmière psychiatrique, dans un contexte de prestation de soins en français à Ottawa, pendant la période de désinstitutionnalisation psychiatrique. L’étude de cas d’une patiente francophone suivie pendant 26 ans à la clinique externe de l’Hôpital Montfort a été choisie comme échantillon. Durant son parcours de vie psychiatrique, 63 % des contacts de cette patiente ont été avec l’infirmière, 27 % avec les psychiatres, 5 % avec les ergothérapeutes, 4 % avec les travailleurs sociaux et 1 % avec les psychologues. Parmi les différentes tâches documentées par les infirmières, on retrouve six différents types d’intervention. Le dossier étudié révèle donc que l’infirmière occupe un espace relationnel plus important que les autres professionnels de l’équipe multidisciplinaire. Mots-clés : infirmière, santé mentale, désinstitutionnalisation psychiatrique, équipe multidisciplinaire, parcours de vie

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Research Component. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon. Executive summary - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Volet Recherche. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Pratique # 26 : Accès santé jeunesse Péninsule acadienne (ASJPA) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province (Sommaire) - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)

The Needs of Francophones and Acadians in Five Communities in the Province (Summary Report). - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Quand le terrain informe les interventions communautaires. - van Kemenade, Solange; Tremblay, Éléonore; Benhamadi, Bey; Moussard, Aline; Michel, Jean Nephetaly (Minorités linguistiques et société, 2024)
L’Abécédaire d’un cerveau en santé – Sensibilisation à la démence dans l’Ouest et le Nord est un projet chapeauté par RésoSanté Colombie-Britannique et mis en oeuvre en partenariat avec les réseaux de Santé en français de la Saskatchewan, de l’Alberta et du Yukon. Ses objectifs étaient : a) produire des connaissances pour mieux comprendre la problématique de la démence et son impact dans les communautés francophones dans les provinces et le territoire ciblés; b) prévenir la démence et réduire la stigmatisation des personnes atteintes de troubles neurodégénératifs. Cet article se concentre sur le volet recherche du projet qui a accompagné l’intervention communautaire. Des entrevues semi-structurées (N=29) et un sondage en ligne (N=282) auprès des communautés francophones, des personnes proches aidantes, des intervenantes et des intervenants ainsi que du personnel oeuvrant dans les organisations de la francophonie ont été réalisées. L’étude a contribué à documenter la nécessité de services de prévention, de diagnostic, de soutien et de soins en français en matière de troubles neurocognitifs, à repérer des populations plus vulnérables et à recenser des bonnes pratiques. La recherche sur le terrain a éclairé les responsables et les partenaires du projet dans le choix des interventions communautaires appropriées en matière de prévention et de sensibilisation dans un contexte linguistique minoritaire. Mots-clés : troubles cognitifs, démence, francophones en situation minoritaire, interventions communautaires, Canada

Active offer, bilingualism, and organizational culture - Vézina, Sylvain (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre active, bilinguisme et culture organisationnelle - Vézina, Sylvain (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce texte, l’auteur aborde l’offre active sous l’angle de la culture organisationnelle. Il y présente les résultats d’une enquête menée auprès de professionnels de la santé oeuvrant au sein d’établissements hospitaliers anglophones et francophones du Nouveau-Brunswick. La culture organisationnelle y est traitée, à la lumière de la sociologie des organisations, non pas comme une fatalité, mais comme un construit, au même titre que les règles du jeu organisationnel (rapports hiérarchiques, définition des tâches, conventions collectives…). Cette recherche fait ressortir la prédominance d’une culture organisationnelle centrée sur le bilinguisme donnant lieu à la persistance d’une confusion entre les notions d’offre active et de bilinguisme. Or, du point de vue de l’auteur, si le bilinguisme est essentiel à l’offre de services de qualité dans les deux langues officielles, il peut être contre-productif quand il s’agit d’introduire une culture favorable à l’offre active. Il affirme, en effet, que l’accent mis sur le bilinguisme est souvent perçu par les personnes unilingues comme une menace à l’équilibre des forces au sein du système entraînant, le plus souvent, de la résistance envers toute mesure favorable à l’offre active. C’est pourquoi il en vient à suggérer la valorisation d’une culture d’offre active autour d’objectifs de sécurité et de qualité des soins dans les langues officielles. Mots-clés : professionnels de la santé, établissements hospitaliers, culture organisationnelle, bilinguisme, offre active, Nouveau-Brunswick

Active offer, actors, and the health and social service system: An analytical framework - Vézina, Sylvain; Savard, Sébastien (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre active, acteurs et système de santé et de services sociaux : un cadre d’analyse - Vézina, Sylvain; Savard, Sébastien (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Ce chapitre présente un cadre théorique inspiré de l’analyse stratégique aussi nommée sociologie des organisations. Par cette approche, le chercheur tente de découvrir les objectifs et stratégies des acteurs en présence pour mieux saisir la dynamique du système d’action tout en prenant en compte les contraintes issues de la structure formelle. On y traite des concepts de système d’action, de pouvoir, de règle du jeu, de changement, de stratégie, d’acteur, d’enjeu, d’organisation et d’environnement, lesquels rendent compte de la complexité des défis entourant la pratique de l’offre active en santé et services sociaux. Une des contributions majeures de cette approche est qu’elle fournit un cadre d’analyse permettant de mieux saisir la relation entre l’acteur et le système, deux composantes essentielles tant à la compréhension de notre objet qu’à l’identification de stratégies d’action par les acteurs du milieu. Mots-clés : offre active, services sociaux et de santé, système d’action, pouvoir, zone d’incertitude, analyse stratégique, sociologie des organisations, changement, stratégie, acteur, enjeu, organisation, environnement.

Création d'une grille d'observation pour simulations sur l'offre active de services de santé en français - Vincent, Coralie; Bodnaruc, Alexandra Maria; Kengneson, Cris-Carelle; Savard, Jacinthe; Giroux, Isabelle (Reflets, 2021)
Au Canada, il fut démontré que les communautés francophones vivant en situation linguistique minoritaire éprouvent des difficultés à se prévaloir de services sociaux et de santé dans leur langue de préférence, ce qui peut négativement affecter la qualité et la sécurité des services. L’offre active est une pratique visant à contrer les effets de la minorisation linguistique en invitant, de manière proactive et dès le premier contact, les bénéficiaires à s’exprimer dans la langue officielle de leur choix. Il n’existe actuellement aucun outil validé permettant l’évaluation de cette compétence auprès des futurs professionnels des domaines de la santé et des services sociaux. Cet article présente les étapes de création et de validation de Grille d’observation des indicateurs de compétence la en offre active de services en français, laquelle vise à soutenir les programmes de formation dans l’enseignement et l’évaluation de cette compétence au moyen de simulations. Mots-clés : minorités linguistiques, offre active de services en français, langue et services, qualité des soins, formation professionnelle en santé et service social, grille d’observation, validation

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.

Language barriers to healthcare for linguistic minorities: The case of second language-specific health communication anxiety - Zhao, Yue; Segalowitz, Norman; Voloshyn, A.nastasiya; Chamoux, Estelle; Ryder, Andrew G. (Health Communication, 2021)
In this study we examined health communication anxiety (HCA) associated with language-discordant situations – that is, where people have to use their second language (L2) to communicate with health providers who are using their first language (L1). We adapted existing HCA scales in order to (1) assess L2 HCA in such situations separately for physical and mental/emotional health contexts and (2) control for potential confounds, such as HCA not related to L2 use and L2 communication anxiety not related to health, allowing us to obtain L2-specific measures of HCA. We examined the relationship between L2-specific HCA and willingness to use health services in language-discordant situations. English-speaking linguistic minority participants (N = 314) living in Québec, a predominantly French-speaking area of Canada, were recruited for online testing. The results revealed that, separately for both physical and mental/emotional health contexts, there were significant and meaningful L2-specific relations between HCA and willingness to use L2 health services – i.e., over and above general anxiety and discomfort about using an L2, and over and above general health communication anxiety. The effect was stronger for mental/emotional health contexts. The results are discussed in terms of their implications for understanding barriers to health services for linguistic minorities.